2008
DOI: 10.1016/j.jvs.2008.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasound changes in the great saphenous vein after endosaphenous laser occlusion with 808-nm wavelength

Abstract: The healing process is based on vein thrombosis, fibrosis, and venous atrophy. Saphenofemoral interruption makes venous occlusion easier and prevents potential thrombotic complications and recurrence by recanalization. DUS monitoring makes possible to follow-up the thrombus involution and perform early retreatment. The 808-nm endosaphenous laser should be mainly applied to veins of <10 mm in diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
2
14
0
3
Order By: Relevance
“…The same investigators then followed a separate group of 44 limbs treated with 12 to 15 watts, at an average of 30 to 40 J/cm, without tumescent anesthesia, and found 41% of veins either partially or completely recanalized. 18 Mordon et al 11 reported transmural injury in a mathematical model, using a water-specific 1320-nm laser which corroborates why our Dominican patients felt pain with the water-specific 1470-nm device (nociceptive nerve fibers reside in the aventitia). The fact that there were no heat-induced complications without a perivenous heat sink in the Dominican patients is consistent with published basic science literature.…”
Section: Discussionsupporting
confidence: 75%
“…The same investigators then followed a separate group of 44 limbs treated with 12 to 15 watts, at an average of 30 to 40 J/cm, without tumescent anesthesia, and found 41% of veins either partially or completely recanalized. 18 Mordon et al 11 reported transmural injury in a mathematical model, using a water-specific 1320-nm laser which corroborates why our Dominican patients felt pain with the water-specific 1470-nm device (nociceptive nerve fibers reside in the aventitia). The fact that there were no heat-induced complications without a perivenous heat sink in the Dominican patients is consistent with published basic science literature.…”
Section: Discussionsupporting
confidence: 75%
“…The application of 30 to 40 J/cm of energy into the GSV and SSV leads to necrosis and coagulation of the intima and internal media, thrombosis, fibrosis, and venous hypotrophy. Atrophy was observed over a mean period of 12 months in the previous studies 16–18 . A similar mechanism of action was also confirmed for higher wavelengths of 980 and 1,320 nm 19,20 …”
supporting
confidence: 75%
“…5 Histological analysis of endothermally-treated GSVs after 1 to 2 months showed large empty areas covered with endothelium in all 8 cases. However, some microvessels were located in the center of the neointima embedded in extensive fibrosis.…”
Section: Discussionmentioning
confidence: 85%